In vitro analysis of different properties of acrylic resins for ocular prosthesis submitted to accelerated aging with or without photopolymerized glaze - Santos, Daniela Micheline dos [UNESP]; Nagay, Bruna Egumi [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Sonego, Mariana Vilela [UNESP]; Moreno, Amália; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP]; Goiato, Marcelo Coelho [UNESP] (Elsevier, 2016)
The effect of a photopolymerized glaze on different properties of acrylic resin (AR) for ocular prostheses submitted to accelerated aging was investigated. Forty discs were divided into 4 groups: N1 AR without glaze (G1); colorless AR without glaze (G2); N1 AR with glaze (G3); and colorless AR with glaze (G4). All samples were polished with sandpaper (240, 600 and 800-grit). In G1 and G2, a 1200-grit sandpaper was also used. In G3 and G4, samples were coated with MegaSeal glaze. Property analysis of color stability, microhardness, roughness, and surface energy, and assays of atomic force microscopy, scanning electron microscopy, and energy-dispersive spectroscopy were performed before and after the accelerated aging (1008 h). Data were submitted to the ANOVA and Tukey Test (p < 0.05). Groups with glaze exhibited statistically higher color change and roughness after aging. The surface microhardness significantly decreased in groups with glaze and increased in groups without glaze. The surface energy increased after the aging, independent of the polishing procedure. All groups showed an increase of surface irregularities. Photopolymerized glaze is an inadequate surface treatment for AR for ocular prostheses and it affected the color stability, roughness, and microhardness. The accelerated aging interfered negatively with the properties of resins.
Keywords: Acrylic resins; Artificial eye; Color; Hardness; Surface properties